Interpreting Arc and Line Shapes in the Fault Ruptures of the 2016 Mw7.8 Kaikoura, New Zealand and the 2023 Mw7.8 and Mw7.6 East Anatolian Fault, Turkey-Syria Earthquakes: A Theoretical Approach - Daryono, Mudrik Rahmawan; de Gelder, Gino; Patria, Adi (Journal of Engineering and Technological Sciences, 2024)
This study examined the arc and line shapes produced in the fault ruptures of the 2016 Mw7.8 Kaikoura earthquake in New Zealand and the 2023 Mw7.8 and Mw7.6 East Anatolian Fault earthquakes in Turkey-Syria. Theoretical fault mechanisms and physical laws of movement were used to interpret the conceptual geometry of the arc and line shapes, and kinematics force movement. Using computer-aided design (CAD) on the Universal Transverse Mercator (UTM) metric projection, this paper presents earthquake parameters defining the fault geometry, including straight lines and arc shapes with specific measurements such as radius, length, angles, and normal/perpendicular vectors. Comparative analysis revealed distinctions between the two seismic events. Specifically, the Kaikoura earthquake exhibited a smaller normal vector compared to the Turkey-Syria earthquakes. Further interpretation uncovered that the Kaikoura earthquake resulted from pressure exerted by the radius arc vector from both the south-east and north-west, aligning with the continuation of the north-easternmost fault rupture. This suggests that the primary fault vector aligns with the fault trend. In contrast, the Turkey-Syria earthquakes displayed two independent circuit systems. The first event in the Turkiye-Syria rupture underwent an orientation change or bending of about 137 degrees (from N24oE to N68oE). The normal vector of the second earthquake originated from the bending angle of the first earthquake, close to its hypocenter. The rupture of the Kaikoura earthquake followed a lineament orientation of N47oE, forming an approximately 10-km wide corridor, comprising both straight lines and arc shapes.